Electron and ion transmission of the gating foil for the TPC in the ILC experiment. (April 2020) - Kobayashi, M; Ogawa, T; Shoji, A; Aoki, Y; Ikematsu, K; Gros, P; Kawaguchi, T; Arai, D; Iwamura, M; Katsuki, K; Koto, A; Yoshikai, M; et al.
Abstract: We have developed a gating foil for the time projection chamber envisaged as a central tracker for the international linear collider experiment. It has a structure similar to the Gas Electron Multiplier (GEM) with a higher optical aperture ratio and functions as an ion gate without gas amplification. The transmission rate for electrons was measured in a counting mode for a wide range of the voltages applied across the foil using an 55 Fe source and a laser in the absence of a magnetic field. The upper limit of the transmission rate for positive ions was estimated to be 3.36 ± 0.05 (stat. only)) × 10 −4 from the measured electron transmission at a relatively low reverse bias voltage applied to the foil (Δ V =−15.5 V). The blocking power of the gating foil was confirmed to be high enough to suppress the influence of ion backflow.